To evaluate the expression \( 5x^2 + 2y \) when \( x = -3 \) and \( y = 0.25 \), we first substitute the values of \( x \) and \( y \) into the expression.
-
Calculate \( x^2 \): \[ x^2 = (-3)^2 = 9 \]
-
Substitute \( x^2 \) into the expression \( 5x^2 \): \[ 5x^2 = 5 \times 9 = 45 \]
-
Substitute \( y \) into the expression \( 2y \): \[ 2y = 2 \times 0.25 = 0.5 \]
-
Now combine the results: \[ 5x^2 + 2y = 45 + 0.5 = 45.5 \]
Therefore, the evaluated result of the expression \( 5x^2 + 2y \) when \( x = -3 \) and \( y = 0.25 \) is \( \boxed{45.5} \).